Hubungan Perilaku Self-Injury terhadap Regulasi Emosi pada Remaja Akhir - Aullyasari Rhengganis; Sri Nugroho Jati; Rizki Fitlya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to produce a product for the development of a learning media using Easil in news text materials for grade VII students at SMP Negeri 2 Lawang Kidul. The type of researcher used is the RnD (Research and Development) method. The development model used is using the Alessi & Trolip development model.Learning media using Easil in news text materials for grade VII students at SMP Negeri 2 Lawang Kidul was developed based on the results of needs analysis and interviews of teachers and students. In the results of the needs analysis and interviews of teachers and students, learning media products using Easil are needed in learning news text material for grade VII students at SMP Negeri 2 Lawang Kidul. Next, the first step is to carry out the initial design of product manufacturing by making flowcharts and storyboards. Then the next step is the development of the initial form of the product, validation tests, and product revisions. The validation test has 3 aspects, namely, the media aspect which gets a percentage result of 92.86% with a very feasible category. Furthermore, in the material aspect with a percentage of 87.5% with a very decent category. Furthermore, the last aspect is the language aspect with a percentage result of 79.17% with a very decent category. From all three aspects, it was obtained in the category of very suitable for use in the learning media from research on the development of learning media using Easil in news text materials for grade VII students at SMP Negeri 2 Lawang Kidul.